Reflections on the Drive to Return Mission Schools to their Owners in Nigeria - Matthew, Ige Akindele (Contemporary Research in Education and English Language Teaching, 2021)
The issue of whether the government in Nigeria should return the schools taken from the religious organizations over four decades ago is a topic for debate. While many are arguing that such schools should be returned to their owners, others, want the government to stay action on it. It however needs not be over-emphasized that the policy of government control of schools has to a large extent guaranteed equal educational opportunities, quality education provision, increased access to education, religious tolerance, and improved national unity. When viewed from another perspective, can Nigeria afford to take another risk by returning the schools to the Missions, more so that issues of unemployment, high cost of education, religious intolerance, among others, are prevalent in the country, which the return of the schools will promote to a high level? In this paper, the roles which the Christian Missions played in the educational system were examined while the arguments for and against this initiative were examined. It is hopeful that with adequate financing, effective supervision of schools, standards put in place by the government, the agitation of people for the return of schools to the original owners will become history.